Introduction to microelectronics to nanoelectronics design and technology - Majumder, Monoj Kumar; Kumbhare, Vijay Rao; Japa, Aditya; Kaushik, Brajesh Kumar (Microelectronis, 2021)
Focussing on micro- and nanoelectronics design and technology, this book provides thorough analysis and demonstration, starting from semiconductor devices to VLSI fabrication, designing (analog and digital), on-chip interconnect modeling culminating with emerging non-silicon/ nano devices. It gives detailed description of both theoretical as well as industry standard HSPICE, Verilog, Cadence simulation based real-time modeling approach with focus on fabrication of bulk and nano-devices. Each chapter of this proposed title starts with a brief introduction of the presented topic and ends with a summary indicating the futuristic aspect including practice questions. Aimed at researchers and senior undergraduate/graduate students in electrical and electronics engineering, microelectronics, nanoelectronics and nanotechnology, this book:- Provides broad and comprehensive coverage from Microelectronics to Nanoelectronics including design in analog and digital electronics.- Includes HDL, and VLSI design going into the nanoelectronics arena.- Discusses devices, circuit analysis, design methodology, and real-time simulation based on industry standard HSPICE tool.- Explores emerging devices such as FinFETs, Tunnel FETs (TFETs) and CNTFETs including their circuit co-designing.- Covers real time illustration using industry standard Verilog, Cadence and Synopsys simulations